426 Retrospective study of early stage endometrial cancer in portsmouth hospital NHS trust, UK an audit on adherence of united kingdom guidelines and overall survival. (18th September 2019) - Lwin, M; Uherek, M; Khoury, G; Gardner, F; Yeoh, CC
Abstract : Objectives: We audited the management of early stage (Stage 1) endometrial cancer in our institution's adherence with British Gynaecological Cancer Society (BGCS) guidelines. The guidelines state 1) Hysterectomy and bilateral salpingo-oopherectomy is recommended for Grade 1–2 disease. Lymphadenectomy is not recommended in low risk cases. 2) Low risk disease does not require adjuvant treatment, 3) For intermediate risk, adjuvant vaginal vault brachytherapy is recommended. 4) For high intermediate risk to consider external beam radiotherapy if nodal status unknown and to consider vaginal brachytherapy if node negative. 5) For high risk to consider EBRT vs vaginal brachytherapy. Methods: All stage I endometrial cancer patients registered to our institution from June 2015 to March 2018 were selected from database. Electronic record of case notes, histology, blood results, imaging results and multi-disciplinary team meeting outcomes were retrospectively reviewed. Results: A total of 120 patients, age 32–88 years (median age 65 years). 113 patients underwent surgery (87 had TH + BSO and 26 had TH+BSO+lymphadenectomy). 7 patients were not fit for surgery and treated with hormone. Post op histology showed 76 patients G1, 20 patients G2 and 17 patients G3. 111 patients had FIGO IA and 2 patients had IB. 26 patients were given adjuvant radiotherapy (3 EBRT and 23 Brachytherapy). Conclusions: Rate of adherence with BGSC guidelines for surgery and adjuvant radiotherapy were 90% and 88.5% respectively. Some grade changes between pre and post-op histology, findings in clinical examination and imaging were attributed to the main management reason to treat outside BGCS guidelines. Recurrent rate was 2.5%.